Synthesis, Characterization, and Optimization Studies of Polycaprolactone/Polylactic Acid/Titanium Dioxide Nanoparticle/Orange Essential Oil Membranes for Biomedical Applications - Zapata-Ramirez, P; Saavedra-Gonzalez, M (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The development of scaffolds for cell regeneration has increased because they must have adequate biocompatibility and mechanical properties to be applied in tissue engineering. In this sense, incorporating nanofillers or essential oils has allowed new architectures to promote cell proliferation and regeneration of new tissue. With this goal, we prepared four membranes based on polylactic acid (PLA), polycaprolactone (PCL), titanium dioxide nanoparticles (TiO2-NPs), and orange essential oil (OEO) by the drop-casting method. The preparation of TiO2-NPs followed the sol–gel process with spherical morphology and an average size of 13.39 nm ± 2.28 nm. The results show how the TiO2-NP properties predominate over the crystallization processes, reflected in the decreasing crystallinity percentage from 5.2% to 0.6% in the membranes. On the other hand, when OEO and TiO2-NPs are introduced into a membrane, they act synergistically due to the inclusion of highly conjugated thermostable molecules and the thermal properties of TiO2-NPs. Finally, incorporating OEO and TiO2-NPs promotes tissue regeneration due to the decrease in inflammatory infiltrate and the appearance of connective tissue. These results demonstrate the great potential for biomedical applications of the membranes prepared. © 2022 by the authors.